2011
DOI: 10.1108/17542411111175469
|View full text |Cite
|
Sign up to set email alerts
|

Audit committee gender differences and earnings management

Abstract: Purpose -The purpose of this paper is to investigate whether gender diversity of audit committees has a significant impact on the firm's earnings management. Design/methodology/approach -This paper uses a performance-adjusted discretionary accrual model to examine the association between gender variables and the firm's earnings management. Regression analysis is applied using 320 firms from the S&P Small Cap 600. Findings -The authors find consistent evidence to show that the presence of a female director on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
153
8
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(181 citation statements)
references
References 24 publications
16
153
8
4
Order By: Relevance
“…In a similar vein, Krishnan and Parsons (2008) found that the quality of earnings management is higher for firms with more female directors, and argued that women are likely to be more ethical in their judgement and behaviour than men. However, in contrast to these findings, Sun et al (2011) found no evidence of the impact of female representation on audit committees and earnings management, while Thiruvadi and Huang (2011) found that the presence of female directors on the audit committee is negatively related to earnings management. In light of the differing views, we are enquiring into the relationship between female directors and earnings management in the UK.…”
Section: Female Directors and Earnings Management -The Key Questionscontrasting
confidence: 44%
“…In a similar vein, Krishnan and Parsons (2008) found that the quality of earnings management is higher for firms with more female directors, and argued that women are likely to be more ethical in their judgement and behaviour than men. However, in contrast to these findings, Sun et al (2011) found no evidence of the impact of female representation on audit committees and earnings management, while Thiruvadi and Huang (2011) found that the presence of female directors on the audit committee is negatively related to earnings management. In light of the differing views, we are enquiring into the relationship between female directors and earnings management in the UK.…”
Section: Female Directors and Earnings Management -The Key Questionscontrasting
confidence: 44%
“…GENDER is the explanatory variable representing the audit committee's gender diversity. As per Ittonen, et al (2010) and Thiruvadi and Huang (2011), we use three proxies to measure diversity: FSIZE denotes the number of women members; FEM is a dummy variable set to 1 if there is at least one female on the audit committee; and FPCT denotes the percentage of female members to total number of directors on the committee.…”
Section: Methodsmentioning
confidence: 99%
“…independence, expertise and activity) and association between audit committee quality, auditor independence and internal control (Bedard, Chtourou & Courteau, 2004;Carcello & Neal, 2000;Zhang, Zhou & Zhou,2007). Recently, some studies find that gender diversity of audit committees plays an important role in corporate governance (Gavious, Segev& Yosef, 2012;Ittonenet al 2010;Thiruvadi & Huang, 2011), but these studies are based on U.S. data and generally do not examine situations unique to emerging and transitional nations, thus their findings may not be applicable to Chinese firms.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Regarding earnings management, prior studies reveal that the quality of earnings is higher for firms with more women directors (Krishnan & Parsons, 2008;Peni & Vähämaa, 2010;Thiruvadi & Hua-Wei Huang, 2011). Further, Gavious et al (2012) and Barua, Davidson, Rama, and Thiruvadi (2010) reveal that firms with women CEOs have fewer earnings management than those with males, and document a negative relationship between women executives and earnings management.…”
Section: Hypotheses Developmentmentioning
confidence: 99%